Timing of Sandeel Spawning and Hatching Off the East Coast of Scotland - MacDonald, Alan; Heath, Michael R.; Greenstreet, Simon P. R.; Speirs, Douglas C. (Frontiers in Marine Science, 2019)
The lesser sandeel, Ammodytes marinus, is a key forage fish species in the North Sea. Mean lengths and abundances of sandeels have declined steeply since 1990’s and these are associated with declining breeding success of various seabird species on the east coast of Scotland, especially kittiwakes. The declining lengths have led to a mismatch between the peak in food demand arising from chick rearing, and the appearance of appropriately sized young sandeels in the foraging areas of the birds. A 10-year time series of sandeel larval samples between 2000 and 2009 offer a rare opportunity to analyze trends in spawning and hatch dates and determine whether they contributed to changes in mean lengths. By analyzing the abundance, length and age distributions of sandeel larvae we were able to determine the temporal distribution of hatching rates each year, and back-track to the likely spawning dates of the sandeels. Estimated spawning dates showed no evidence of correlation with environmental cues such as tidal or lunar phases. However, hatch end dates varied by 20 days over the 10-year period and were correlated with the date of the seasonal minimum of sea bottom temperature. We show a significant decline between growth rate and 0-group length between 2000 and 2009, and suggest that changes in food quality and availability, rather than shifts in hatch dates, are likely to be responsible for current declines in the availability of sandeels to seabirds.